1996
DOI: 10.1063/1.118009
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature epitaxy of Pd films on GaN under conventional vacuum conditions

Abstract: Pd films deposited at room temperature have been found to grow epitaxially on GaN grown by metalorganic vapor phase epitaxy (MOVPE). The Pd films were deposited on GaN substrates cleaned by chemicals only, and in a conventional e-beam evaporation system with a vacuum of ∼1×10−7 Torr. MeV 4He backscattering spectrometry and the Read x-ray camera were used to evaluate the Pd films. The effects of various chemical etchants—such as aqua regia, HCl:H2O, and HF:H2O—on the epitaxial quality of the Pd films have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Their results were inconsistent. In some reports, palladium uniformly covered the surface and grew epitaxially [14,15]; in others, the Pd films had grainy structure [16]. Some results showed 3D palladium nanoislands as well as surface and bulk alloys formed after annealing [17,18]; other research excluded the formation of alloys or interfacial compounds [19].…”
Section: Introductionmentioning
confidence: 93%
“…Their results were inconsistent. In some reports, palladium uniformly covered the surface and grew epitaxially [14,15]; in others, the Pd films had grainy structure [16]. Some results showed 3D palladium nanoislands as well as surface and bulk alloys formed after annealing [17,18]; other research excluded the formation of alloys or interfacial compounds [19].…”
Section: Introductionmentioning
confidence: 93%
“…16 For other metal films, such as Pd, on GaN ͑0001͒, however, a channeling yield as low 16% has been observed. 12 Since RHEED patterns and x-ray thin-film camera results indicated that Al overgrowth was of good crystalline quality and the RHEED patterns showed that ͗110͘ GaN ʈ͗211͘ Al and ͗1100͘ GaN ʈ͗011͘ Al , we may conclude that a definite crystallographic relationship between the Al overlayer and the GaN substrates exists, i.e., Al is ''epitaxial'' on GaN and not merely highly textured.…”
mentioning
confidence: 95%
“…11 Recently, we have found that Pd, Ni, and Pt can be grown epitaxially on GaN in a conventional e-beam evaporation system without in situ cleaning in UHV. 12 Other metals, such as Au, Al, Ti, and Hf, have also been found to grow epitaxially on GaN under conventional vacuum conditions. 13 These findings suggest that after the GaN surface has been cleaned by acid etching, the presence of oxides on GaN surfaces is minimal and, furthermore, that native oxides do not grow rapidly on the GaN surface during the time ͑Ͻ30 min͒ required to load the samples in the vacuum deposition chamber.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Palladium is capable of forming low resistance contacts to p-GaN (and good Schottky contacts to n-GaN), provided that the wafer surface has been cleaned properly [4][5][6][7][8]. Under certain conditions, the palladium may deposit epitaxially in an electron beam evaporator [9]. The silver serves as a good reflector, and the nickel and gold have been added for wirebonding purposes.…”
Section: Device Designmentioning
confidence: 99%